Influence of fall armyworm previous experience with soybean genotypes on larval feeding behavior - Boica Junior, Arlindo L. [UNESP]; Souza, Bruno H. S. [UNESP]; Costa, Eduardo N. [UNESP]; Paiva, Leonardo B. [UNESP] (Springer, 2017)
Previous experience on host plants can modify insect feeding behavior. Because insect habituation and induction of preference to host plants are variable across species of plants and insects, it is necessary to investigate each insect-plant interaction to determine whether this phenomenon occurs or not in the system. In this study we investigated the potential occurrence of habituation and induction of preference in fall armyworm (FAW) Spodoptera frugiperda to soybean genotypes. Neonate FAW larvae reared on artificial diet were divided into four treatment groups and fed for one generation with either the resistant soybeans PI 227687 or IAC 100 or the susceptible soybeans BRS Valiosa RR or IGRA RA 626 RR. Biological parameters of FAW were recorded. Eggs obtained from FAW of each genotype group were separated, and the newly hatched larvae were fed on the same genotypes experienced by their parents for additional 8 days. FAW larval preference and leaf area consumed were evaluated in choice feeding assays with the four soybean genotypes within a 24-h period. Genotypes PI 227687 and IAC 100 negatively affected FAW development, demonstrating they are FAW-resistant. FAW larvae exposed to both resistant genotypes consumed more foliage of genotype IGRA RA 626 RR in the choice assays, whereas larvae reared on both susceptible genotypes did not show any preference. From our preliminary study, FAW does not show habituation and induction of preference toward the experienced soybean genotypes. The importance of our findings to host plant resistance and insect-plant biology fields is discussed.
Keywords: Learning; Habituation; Induction of preference; Sensitization; Spodoptera frugiperda